Epigenetic Regulation in the Pathogenesis of Sjögren Syndrome and Rheumatoid Arthritis - Ibáñez-Cabellos, José Santiago; Seco-Cervera, Marta; Osca-Verdegal, Rebeca; Pallardó, Federico V.; García-Giménez, José Luis (Frontiers in Genetics, 2019)
Autoimmune rheumatic diseases, such as Sjögren syndrome (SS) and rheumatoid arthritis (RA), are characterized by chronic inflammation and autoimmunity, which cause joint tissue damage and destruction by triggering reduced mobility and debilitation in patients with these diseases. Initiation and maintenance of chronic inflammatory stages account for several mechanisms that involve immune cells as key players and the interaction of the immune cells with other tissues. Indeed, the overlapping of certain clinical and serologic manifestations between SS and RA may indicate that numerous immunologic-related mechanisms are involved in the physiopathology of both these diseases. It is widely accepted that epigenetic pathways play an essential role in the development and function of the immune system. Although many published studies have attempted to elucidate the relation between epigenetic modifications (e.g. DNA methylation, histone post-translational modifications, miRNAs) and autoimmune disorders, the contribution of epigenetic regulation to the pathogenesis of SS and RA is at present poorly understood. This review attempts to shed light from a critical point of view on the identification of the most relevant epigenetic mechanisms related to RA and SS by explaining intricate regulatory processes and phenotypic features of both autoimmune diseases. Moreover, we point out some epigenetic markers which can be used to monitor the inflammation status and the dysregulated immunity in SS and RA. Finally, we discuss the inconvenience of using epigenetic data obtained from bulk immune cell populations instead specific immune cell subpopulations.